Designed SARS‐CoV‐2 receptor binding domain variants form stable monomers. Issue 5 (3rd February 2022) - Klausberger, Miriam; Kienzl, Nikolaus F.; Stadlmayr, Gerhard; Grünwald‐Gruber, Clemens; Laurent, Elisabeth; Stadlbauer, Katharina; Stracke, Florian; Vierlinger, Klemens; Hofner, Manuela; Manhart, Gabriele; Gerner, Wilhelm; Grebien, Florian; et al.
Abstract: The receptor binding domain (RBD) of the SARS‐CoV‐2 spike (S)‐protein is a prime target of virus‐neutralizing antibodies present in convalescent sera of COVID‐19 patients and thus is considered a key antigen for immunosurveillance studies and vaccine development. Although recombinant expression of RBD has been achieved in several eukaryotic systems, mammalian cells have proven particularly useful. The authors aimed to optimize RBD produced in HEK293‐6E cells towards a stable homogeneous preparation and addressed its O‐glycosylation as well as the unpaired cysteine residue 538 in the widely used RBD (319‐541) sequence. The authors found that an intact O‐glycosylation site at T323 is highly relevant for the expression and maintenance of RBD as a monomer. Furthermore, it was shown that deletion or substitution of the unpaired cysteine residue C538 reduces the intrinsic propensity of RBD to form oligomeric aggregates, concomitant with an increased yield of the monomeric form of the protein. Bead‐based and enzyme‐linked immunosorbent assays utilizing these optimized RBD variants displayed excellent performance with respect to the specific detection of even low levels of SARS‐CoV‐2 antibodies in convalescent sera. Hence, these RBD variants could be instrumental for the further development of serological SARS‐CoV‐2 tests and inform the design of RBD‐based vaccine candidates. Graphical Abstract and Lay Summary: The receptor binding domain (RBD) of the SARS‐CoV‐2 spike protein is a prime target of virus‐neutralizing antibodies present in convalescent sera of COVID‐19 patients, and considered a key antigen for immunosurveillance studies and vaccine development. The authors show that deletion or substitution of the unpaired cysteine residue C538 increases the tendency of RBD to form stable monomers and such mutants are suitable for serum screening . Further, intact O‐glycosylation at T323 position was found also highly relevant for the stability of RBD.